Improvement in knowledge following a blended e-learning and simulation training course for operative vaginal delivery. (18th April 2012) - Sullivan, CD; Bahl, R; Strachan, BK
Abstract : Background: Operative vaginal delivery (OVD) remains an integral element of intrapartum care. With the reduction of trainees' hours and the move to competency based training, there is a requirement for a formal training package in operative vaginal delivery to ensure trainees gain core knowledge, confidence and practical experience prior to being exposed to patients. Methods: An interactive e-learning and simulation training course for OVD was developed. All of the ST1's and 2's from Severn Deanery were recruited to participate in the study (n=32). Participants underwent a pre-training assessment, which included an 80 question multiple-choice questionnaire (MCQ). 27/32 participants completed the e-learning modules and attended simulation training. A post-training assessment (where the same MCQ was completed) was carried out to test any improvement in knowledge. Results: There was a 15% drop-out rate (4/5 left to become GP's or train abroad.) A paired t-test was used to compare the data sets. There was a significant improvement (p<0.001) in knowledge by a mean of 10% (95% CI 7.6 to 12.2) with all participants improving their scores following training (Mean score 72% to 82%). Discussion: All participants increased their knowledge about the theoretical aspects of instrumental delivery following completion of this training course. This study has shown that e-learning and simulation are useful methods to improve trainee's knowledge of OVD.